Does the public sector respond to private competition? An analysis of privatization and prison performance - Burkhardt, Brett C. (Journal of crime and justice, 2019)
The competition thesis states that the introduction of competition from private-sector service providers will spur performance improvements in previously monopolistic public-sector service providers, who fear (further) delegation of their responsibilities to the private sector. This article examines the competition thesis in the context of incarceration. Using data on U.S. adult correctional facilities in 2000 and 2005, it employs a difference-in-difference strategy to compare over-time performance changes among newly competitive facilities relative to non-competitive facilities. Prison performance is measured along four dimensions (safety, order, activity, and conditions), using survey responses from prisons. The results do not show a beneficial competition effect; prisons in newly competitive states experienced performance change in ways that were statistically indistinguishable from prisons in non-competitive states. Supplemental analyses reveal this finding to be robust to most modifications to the sample and the model. A discussion considers four reasons - constitutional safeguards, professional standards, labor opposition, and non-credible threats - incarceration may be resistant to a competition effect and the implications for public policy.